2013
DOI: 10.1159/000343896
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Inflammation-Metaplasia-Adenocarcinoma Sequence and Prevention in Surgical Rat Models

Abstract: The incidence of esophageal cancer continues to rise in the Western world. Prior studies have suggested that gastroduodenal content reflux from gastroesophageal reflux disease induces the inflammation-mediated progression from hyperplasia to metaplasia, and to adenocarcinoma. We further investigated the sequential development of esophageal adenocarcinoma (EADC) with the use of an established surgical rat model. The present paper will describe the impact of the inflammation-metaplasia-adenocarcinoma sequence an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…In addition, the conventional treatment for non-erosive reflux disease with gastric acid suppressing medications has been associated with an increased incidence of abnormal microbiota and malignancy [10] . According to a recent study, gastric acid is a strong activator a number of autoprotective mechanisms, including proliferation and differentiation, as well as the production of anti-inflammatory cytokines, growth factors and endogenous antioxidants [4] , [11] , [12] . Conditions such as Barrett’s esophagus, esophageal stricture and esophageal adenocarcinoma, the latter being identified as the most pernicious cancer of the gastrointestinal tract, have sharply risen in incidence over the last decade [9] , [13] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the conventional treatment for non-erosive reflux disease with gastric acid suppressing medications has been associated with an increased incidence of abnormal microbiota and malignancy [10] . According to a recent study, gastric acid is a strong activator a number of autoprotective mechanisms, including proliferation and differentiation, as well as the production of anti-inflammatory cytokines, growth factors and endogenous antioxidants [4] , [11] , [12] . Conditions such as Barrett’s esophagus, esophageal stricture and esophageal adenocarcinoma, the latter being identified as the most pernicious cancer of the gastrointestinal tract, have sharply risen in incidence over the last decade [9] , [13] .…”
Section: Introductionmentioning
confidence: 99%
“…Development of animal models of non-erosive reflux disease would assist in delineating the early events in its pathogenesis, which would hopefully lead to improved therapies. Indeed, several important advances have been made with respect to understanding the early biochemical and molecular mechanisms of ulceration and healing in other parts of the GI tract [12] , [14] [16] .…”
Section: Introductionmentioning
confidence: 99%
“… 19 Though reflux disease is a key factor for development of Barrett’s esophagus, other factors must underlie its development since it occurs in only a minority of reflux disease patients. 20 However, dominant pathogenic mechanism is that gastroduodenal content reflux from gastroesophageal reflux disease induces the inflammation-mediated progression from hyperplasia to metaplasia, and to adenocarcinoma, 21 by which several pharmacological interventions are anticipated as cancer preventive way, including proton pump inhibitor (PPI including esomeprazole, rabeprazole, and pantoprazole), aspirin, NSAIDs, and some more anti-inflammatory agents. The effect of pharmacological and surgical intervention on the natural history of Barrett’s is a subject of ongoing research, including the Barrett’s Esophagus Surveillance Study and the aspirin and proton pump inhibitor (omeprazole) cancer chemoprevention trial with interesting results.…”
Section: Application Of Sitrp In Gastroenterologymentioning
confidence: 99%
“…Lindau et al [17,18,19] reported that the immune system of the tumor bearing host interacts with the tumor throughout its development and hence, this feature serve as a therapeutic target for anti-cancer immunotherapy. A high degree of inflammation was observed in human esophageal cancers [5,8,20,21], animal models of esophageal cancer [22], and esophageal cancer cell lines [23], and this inflammation plays a role in the carcinogenesis of esophageal tumors [5,20,21,24]. Although inflammatory cells have been studied in esophageal squamous cell carcinoma (ESqCC) [10,13,16], esophageal adenocarcinoma [11,25], and other small cell cancers [26], no such information is known in SmCEC.…”
Section: Introductionmentioning
confidence: 99%